2004
DOI: 10.1111/j.1365-201x.2004.01269.x
|View full text |Cite
|
Sign up to set email alerts
|

TNF‐α hyperpolarizes membrane potential and potentiates the response to nicotinic receptor stimulation in cultured rat myenteric neurones

Abstract: TNF-alpha changes the electrophysiological properties of myenteric neurones via cyclooxygenase metabolites and protein tyrosine phosphorylation; the cells primarily responding to the cytokine seem to be non-neuronal cells in the ganglion culture, which respond with a nuclear STAT5 translocation suggesting an action on gene transcription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 45 publications
2
26
0
Order By: Relevance
“…TNF-α plays an important role in IBD [30]. The TNF/TNFR signaling system mediates mucosal damage through the enhancement of NF-ĸB activity by continuous infiltration of TNF-producing cells, probably a key pathogeneses of colitis [31].…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α plays an important role in IBD [30]. The TNF/TNFR signaling system mediates mucosal damage through the enhancement of NF-ĸB activity by continuous infiltration of TNF-producing cells, probably a key pathogeneses of colitis [31].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in a recent study at cultured myenteric ganglia we observed that pre-treatment with TNF-a over night hyperpolarised the membrane potential and potentiated the depolarisation evoked by nicotinic receptor stimulation (Rehn et al, 2004). Thus in the present study we were interested in possible changes of [Ca 2+ ] i after nicotinic receptor stimulation in the presence of this cytokine.…”
Section: Do Mediators Of Inflammation Affect [Ca 2+ ] I Of Myenteric mentioning
confidence: 90%
“…depolarisation evoked by carbachol, which predominantly stimulates nicotinergic receptors at the myenteric ganglia (Rehn et al, 2004). Nifedipine (10 À 5 mol l À 1 ) and CgTx-GVIA (10 À 6 mol l À 1 ) both reduced the increase of the fura-2 fluorescence ratio evoked by carbachol (5 Â 10 À 5 mol l À 1 ; Fig.…”
Section: Response To Cholinergic Receptor Stimulationmentioning
confidence: 97%
See 1 more Smart Citation
“…TNF-␣ also modulates synaptic maturation and neuronal branching in the hippocampus by controlling the expression of synaptic vesicle-associated proteins [84] . Moreover, TNF-␣ changes the electrophysiological properties of myenteric neurons via cyclooxygenase metabolites and protein tyrosine phosphorylation [85] .…”
Section: Tnf-␣mentioning
confidence: 99%